2019
DOI: 10.1101/865212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacteria contribute to plant secondary compound degradation in a generalist herbivore system

Abstract: Herbivores must overcome a variety of plant defenses, including coping with plant secondary compounds (PSCs). To help detoxify these defensive chemicals, several insect herbivores are known to harbor gut microbiota with the metabolic capacity to degrade PSCs. Leaf-cutter ants are generalist herbivores, obtaining sustenance from specialized fungus gardens that act as external digestive systems, degrading the diverse collection of plants foraged by the ants. There is in vitro evidence that certain PSCs harm Leuc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…The existence of chemical gradients in the fungus garden resembles a digestion process, with substrates being modified to facilitate their consumption and generating residues that need to be removed or discarded, as shown here by plant constituents passing through an ant-fungus garden ecosystem. The metabolic transformations observed here are consistent with the modification of lipids by fungus gardens, as well as plant volatile compounds by fungus-garden-associated bacteria, as recently reported from leaf-cutter ant fungus gardens, 23,24 adding further support to the model describing fungus gardens as external digestive systems for ants. The chemical modifications and the types of (bio)transformations observed in our study might not vary based on changes in the available plant material, although environmental factors such as temperature or humidity, and the composition of microbiome that are associated with ants and their fungus gardens, 23 will likely influence these modifications.…”
Section: Mainsupporting
confidence: 90%
“…The existence of chemical gradients in the fungus garden resembles a digestion process, with substrates being modified to facilitate their consumption and generating residues that need to be removed or discarded, as shown here by plant constituents passing through an ant-fungus garden ecosystem. The metabolic transformations observed here are consistent with the modification of lipids by fungus gardens, as well as plant volatile compounds by fungus-garden-associated bacteria, as recently reported from leaf-cutter ant fungus gardens, 23,24 adding further support to the model describing fungus gardens as external digestive systems for ants. The chemical modifications and the types of (bio)transformations observed in our study might not vary based on changes in the available plant material, although environmental factors such as temperature or humidity, and the composition of microbiome that are associated with ants and their fungus gardens, 23 will likely influence these modifications.…”
Section: Mainsupporting
confidence: 90%
“…Farming involves the selection of beneficial fungi over less beneficial (or antagonistic) fungi, a task that is more easily managed by groups of individuals exhibiting division of labor ( 3 ). For ants and termites, it has been shown that bacteria play a prominent role in the farming practices ( 4 ), in particular by defending the fungal crops against pathogens ( 5 , 6 ) but also by nitrogen fertilization of fungus cultivars ( 7 , 8 ) as well as the enzymatic degradation of plant biomass ( 9 , 10 ) and plant defenses ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, no study has monitored the fungal and bacterial communities associated with all the offspring's life stages and throughout the development of a beetle gallery using metabarcoding. This kind of study has revealed roles of specific and apparently essential symbionts in leaf-cutter ants, for example (11). In ambrosia beetles, dynamics of symbionts are poorly known, and therefore, we can currently only make guesses about the roles of specific symbionts and their interactions in the development of the beetles.…”
mentioning
confidence: 99%
“…The nutritional contributions of bacteria within the farming symbiosis are also increasingly coming into focus, as they fix nitrogen (70), metabolize lipids (e.g. lipids, (71)), and can detoxify plant secondary metabolites (72). Within individual leafcutter ants, bacteria can also fix nitrogen (70) and metabolize citrate (33).…”
Section: Discussionmentioning
confidence: 99%